2002
DOI: 10.1097/00005131-200208000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time to Definitive Treatment on the Rate of Nonunion and Infection in Open Fractures

Abstract: The risk of developing an adverse outcome was not increased by aggressive debridement/lavage and definitive fixation up to thirteen hours from the time of injury when early prophylactic antibiotic administration and open fracture first aid were instituted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(140 citation statements)
references
References 17 publications
10
121
1
3
Order By: Relevance
“…In a recent study our group demonstrated a significant increase in the TGF-β1 concentration in fracture haematoma and in serum of patients with long bone fracture. These results indicated the importance of this cytokine for fracture healing and confirmed other clinical and experimental studies [8][9][10][11][12][13][14][15][16][17]. Circulating TGF-β1 levels were found to be a predictor of delayed bone healing and non-union [11].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a recent study our group demonstrated a significant increase in the TGF-β1 concentration in fracture haematoma and in serum of patients with long bone fracture. These results indicated the importance of this cytokine for fracture healing and confirmed other clinical and experimental studies [8][9][10][11][12][13][14][15][16][17]. Circulating TGF-β1 levels were found to be a predictor of delayed bone healing and non-union [11].…”
Section: Introductionsupporting
confidence: 85%
“…Evidence exists that the local and systemic concentrations of different osteogenic growth factors are increased during fracture healing [8][9][10][11][12][13][14][15][16][17]. Among these factors TGF-β1 is known to be pivotal for the bone healing.…”
Section: Introductionmentioning
confidence: 99%
“…8 The management of open fractures is regarded as an orthopaedic emergency. 9 The traditional method of treating open tibial fractures was with an external fixator preferably within six hours of injury. 10,11 Monolateral external fixation has been employed to treat open tibial fractures with great success; however, not without significant complications.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported an infection rate in the tune of 16-66% in open fractures. [1][2][3][4][5][6][7][8] With modern treatment protocols and availability of better antibiotics, this percentage has decreased significantly but still amounts to a sizeable chunk. This scenario is worse for open diaphyseal tibial fractures as they are associated with a higher contamination, soft tissue damage and skin loss.…”
Section: Introductionmentioning
confidence: 99%